Meningkatkan Kemampuan Guru Kelas Dalam Pelaksanaan Proses Pembelajaran Melalui Kegiatan Supervisi Akademik Dengan Teknik Individual - Khairuddin Khairuddin (JURNAL PENA EDUKASI, 2018)
Abstract: This study aims to improve the ability of teachers in the management of learning processes through academic supervision with individual techniques in SD Negeri 050757 Alur Dua subdistricts Sei Lepan Langkat district semester 2 academic year 2015/2016. The results of this study show an increase in the four aspects of the assessment, with an explanation of the improvement on the aspects of preparing the implementation plan at the initial conditions of 54.00 with the criteria value less increased to 66.00 with sufficient value criteria and 76.00 with good value criteria, on the aspect the implementation of learning from the average value of 55.21 with the criteria of less value increased to 65.43 with sufficient value criteria and 75.43 with good value criteria in the second cycle, on the aspect of assessment of learning outcomes from the average of 53.58 with the criteria of value less become 65.42 with enough value criterion and 77.42 with good value criterion as well as on aspect of class management from 54.83 with criterion less value become 66.83 with enough value criterion and 75.83 with good value criterion. Keyword: supervision, individual techniques Abstrak: Penelitian ini bertujuan untuk meningkatkan kemampuan guru dalam pengelolaan proses pembelajaran melalui supervisi akademis dengan teknik individual di SD Negeri 050757 Alur Dua kecamatan Sei Lepan kabupaten Langkat semester 2 Tahun Pelajaran 2015/2016. Hasil penelitian ini menunjukan peningkatan pada keempat aspek penilaian, dengan penjelasan peningkatan pada aspek menyusun rencana pelaksanaan pada kondisi awal dari 54,00 dengan kriteria nilai kurang meningkat menjadi 66,00 dengan kriteria nilai cukup dan 76,00 dengan kriteria nilai baik, pada aspek pelaksanaan pembelajaran dari nilai rata-rata 55,21 dengan kriteria nilai kurang meningkat menjadi 65,43 dengan kriteria nilai cukup dan 75,43 dengan kriteria nilai baik pada siklus kedua, pada aspek penilaian hasil belajar dari rata-rata 53,58 dengan kriteria nilai kurang menjadi 65,42 dengan kriteria nilai cukup dan 77,42 dengan kriteria nilai baik serta pada aspek pengelolaan kelas dari 54,83 dengan kriteria nilai kurang menjadi 66,83 dengan kriteria nilai cukup dan 75,83 dengan kriteria nilai baik. Kata kunci: supervisi, teknik individual